Synthesis of reduced graphene oxide decotate Cu2S nanoparticles for cathode of quantum dot solar cell - Le Doan Duy; Le Thi Ngoc Tu; Le Tien Dat (Universitas Ahmad Dahlan, 2024)
In this paper, the results of making a reduced graphene oxide cathode electrode with Cu2S nanoparticles are shown so that it can be used as a counter electrode in quantum dot solar cells to replace other counter electrodes. An rGO-Cu2S paste obtained by hydrolysis was scanned onto the surface of the fluorine-doped tin oxide (FTO) conductive substrate when bound to Cu2S nano by a screen-printing process, then calcined at 350 °C to crystallize the film. Following calcination, the film was examined for structure using energy-dispersive X-ray (EDX) and X-ray diffraction (XRD) spectroscopy, as well as for type and particle size using scanning and transmission electron microscopy and transmission electron microscopy, respectively. Mott-schottky measurement is used to determine the semiconductor and carrier concentrations in the film, and an electrochemical device is used to assess the electrodes redox capacity in a polysulfide electrolyte solution. The operability of the rGO-Cu2S cathode at the peak of the current density in the C-V curve was 24 mA/cm2, a 30-fold increase compared to that of the Cu2S electrode. This result shows that the efficiency, Voc, FF, Jsc are 4.92%, 0.525 V, 0.418, and 22.4 mA/cm2, respectively.